Energy Efficiency in Palm-Based Food Production Processes in margarine industry through the Utilization of Palm Fiber as Solid Biomass in Boiler Systems: A Comprehensive Review - Zain, Faatin Nisriinaa; Pratiwi, Kharisma Ardhani Nur; Muna, Mochammad Choiril; Zuhriyan Ash Shiddieqy Bahlawan (Universitas Negeri Semarang, 2025)
The increasing demand for margarine, especially in palm oil producing countries like Indonesia, raises concerns about energy consumption and environmental sustainability. This review discusses the potential of palm fiber, a lignocellulosic byproduct of crude palm oil extraction, as a solid biomass fuel to improve energy efficiency in margarine processing industries. A systematic literature review was conducted by analyzing more than sixty peer reviewed journal articles, technical reports, and case studies to evaluate the feasibility and impact of palm fiber utilization. Based on various studies, palm fiber contains 47.9 percent cellulose, has a calorific value of 17.2 megajoules per kilogram, and shows low ash and moisture content, making it suitable for combustion in industrial boilers. Emission data indicate reductions in carbon dioxide, nitrogen oxides, and sulfur oxides compared to fossil fuels, with potential greenhouse gas savings of 0.098 tons of carbon dioxide per gigajoule and sulfur oxide reductions of up to ninety percent. Economically, palm fiber offers cost savings of up to forty percent, with a levelized cost of energy around six United States dollars per gigajoule and a payback period of less than five years. The application of drying and co firing technologies, supported by policy incentives such as Indonesia’s capital expenditure assistance, could enhance adoption. Research gaps remain in terms of long term boiler corrosion and industrial scale briquetting. Overall, palm fiber supports circular economy practices and aligns with SDG 7, 12, and 13, contributing to cleaner energy transitions in palm oil based food production systems.